Analysis of Salmonella contamination and pathogenic characteristics in raw poultry meats in Jiading District， Shanghai in 2021 - CHEN Peichao; HUANG Qiang; SUN Pan; DONG Yuting; PENG Qian (Shanghai yufang yixue, 2023)
ObjectiveTo investigate the contamination status， serotype distribution and drug resistance of Salmonella in retail poultry in Jiading District， Shanghai.MethodsFour types of poultry （chicken， duck， goose and pigeon） have been sampled from commercial markets. Salmonella contamination has been isolated and identified using serotype analysis. Furthermore， resistance of isolated Salmonella strains towards 16 commonly used antibiotics has been determined.ResultsA total of 60 Salmonella strains were isolated from 80 poultry samples. The detection rates of Salmonella in pigeon， goose， duck and chicken were 86.67%， 81.82%， 72.73% and 59.38%， respectively. Contamination status has been categorized by storage conditions. Lowest detection rate （65.63%） has been noted in poultry samples under refrigeration storage. The majority serotypes of Salmonella have been revealed as Salmonella typhimurium， Salmonella enteritidis and Salmonella corvallis. Relatively higher drug resistance was discovered with tetracycline， nalidixic acid， ampicillin and chloramphenicol， with drug resistance rate of 60.00%， 58.33%， 50.00% and 48.33%， respectively. Low drug resistance was revealed with cefotaxime. In addition， these Salmonella strains were completely sensitive to imipenem. Significant difference in drug resistance was identified across the types of poultry or Salmonella serotypes. The 11.67% of Salmonella strains were non-resistant to any tested drugs. Multi-drug resistant strains accounted for 46.67% of isolated strains， which were resistant to 13 different antibiotics. Ampicillin-tetracycline or chloramphenirol-cefazolin drug resistance pattern suggested that the Salmonella strain was multi-drug resistant.ConclusionSalmonella contamination remains high in retail poultry in Jiading District， Shanghai. Drug resistance to antibiotics is increasing. Therefore， monitoring and control of Salmonella should be strengthened.